Targeted Sequencing of Pancreatic Adenocarcinomas from Patients with Metachronous Pulmonary Metastases - Hlavac, Viktor; Mohelnikova-Duchonova, Beatrice; Lovecek, Martin; Ehrmann, Jiri; Brynychova, Veronika; Kolarova, Katerina; Soucek, Pavel (Genes, 2020)
Mutation spectra of 250 cancer driver, druggable, and actionable genes were analyzed in surgically resected pancreatic ductal adenocarcinoma (PDAC) patients who developed metachronous pulmonary metastases. Targeted sequencing was performed in DNA from blood and archival samples of 15 primary tumors and three paired metastases. Results were complemented with the determination of G12V mutation in KRAS by droplet digital PCR. The median number of protein-changing mutations was 52 per patient. KRAS and TP53 were significantly enriched in fractions of mutations in hotspots. Individual gene mutation frequencies or mutational loads accounting separately for drivers, druggable, or clinically actionable genes, did not significantly associate with patients' survival. LRP1B was markedly mutated in primaries of patients who generalized (71%) compared to those developing solitary pulmonary metastases (0%). FLG2 was mutated exclusively in primary tumors compared to paired metastases. In conclusion, signatures of prognostically differing subgroups of PDAC patients were generated for further utilization in precision medicine.
Keywords: nádorový supresorový protein p53; pancreas; pulmonary; survival; Middle Aged; next-generation sequencing; mužské pohlaví; nádory plic; mutace; adenokarcinom; nádory slinivky břišní; Tumor Suppressor Protein p53; Adenocarcinoma; Filaggrin Proteins; proteiny S100; ženské pohlaví; Mutation; Humans; S100 Proteins; filagriny; adenocarcinoma; Pancreatic Neoplasms; lidé středního věku; frekvence genu; Proto-Oncogene Proteins p21(ras); Gene Frequency; metastases; protoonkogenní proteiny p21(ras); Female; Lung Neoplasms; lidé; Male